Women and indigenous communities at the forefront of climate resilience locally driven inclusion mechanisms to transform climate policy in Guatemala and Central America - Paez Valencia, Ana Maria; Valiente, Regina; Lizarazo, Miguel; Borrayo, Andrea; Martinez Baron, Deissy (2025)
This policy brief documents local mechanisms that strengthen the participation and leadership of women and Indigenous Peoples in climate change adaptation processes in Guatemala. Based on case studies carried out in Totonicapán and Chiquimula, in coordination with local partners such as CDRO and ASORECH, the brief analyzes experiences that promote inclusion, access to resources and agroclimatic information, and decision-making from within the territories. The findings highlight the transformative potential of approaches such as community facilitation and women’s engagement in local environmental governance systems, particularly water committees and climate services platforms. In addition, the document offers recommendations at local, national, and regional levels to scale up these experiences, positioning the participation of women and Indigenous Peoples as a key pillar of a more just, effective, and territorially relevant climate policy.